Adiposity indices and their higher predictive value for new-onset hypertension in metabolically healthy young women: findings from a population-based prospective cohort study - Rizki Amalia Gumilang; Yen-Chun Fan; Shang-Hao Wu; Chyi-Huey Bai (BMC Cardiovascular Disorders, 2024)
Abstract Background and aims The present study aimed to investigate the predictive ability of selected adiposity indices, such as body mass index (BMI), waist-to-hip ratio (WHR), waist circumference (WC), and waist-to-height ratio (WHtR), for new-onset hypertension in metabolically healthy Taiwanese adults. The study also sought to establish sex-specific cutoff points for these indices and to analyze the risk of new-onset hypertension, taking into account sex and age. Methods This prospective cohort study utilized the Taiwan Biobank database to examine metabolically healthy participants aged between 20 and 65 at baseline. Four adiposity indices, namely BMI, WHR, WC, and WHtR, were calculated and used to predict new-onset hypertension over 4 years. Receiver operating characteristics (ROCs) and areas under the curve (AUCs) were used to evaluate the effectiveness of the parameters in predicting new-onset hypertension over 4 years. Sex-specific cutoff points were identified and used to assess the risk of new-onset hypertension. Results This study analyzed 13,375 participants over 4.28 years. The incidence of new-onset hypertension was 17.65%. The new-onset rate of hypertension was 34.39% in men and 65.61% in women. Adiposity indices effectively predict new-onset hypertension, with WHtR having the highest predictive value (i.e., AUC) for both sexes. The classification of participants into low and high categories for each adiposity index was based on sex-specific cutoff points, and the risk of new-onset hypertension was assessed according to sex and age. This study found that high adiposity indices predicted a significantly higher risk of new-onset hypertension in metabolically healthy adults. The risk was equal for both sexes. Young women had a higher risk of new-onset hypertension than middle-aged women when they were further categorized. All risk ratios of the indices in young women were over two-fold and significant. Conclusion According to the sex-specific cutoff point, high adiposity indices had a higher predictive value for new-onset hypertension in metabolically healthy Taiwanese young women.